Abundant and Rare Microbial Communities Respectively Contribute to an Aquaculture Pond Ecosystem - Hou, Dongwei; Zhou, Renjun; Wei, Dongdong; Zeng, Shenzheng; Weng, Shaoping; Yan, Qingyun; He, Jianguo; Huang, Zhijian (Frontiers in Marine Science, 2022)
Unraveling the assembly mechanism is a core research topic of microbial ecology. Abundant and rare microbial communities are crucial for diversity, function and host health in a given ecosystem, but few studies focused on their assembly strategies. Here, we explored the microbial diversity of abundant and rare communities of water, shrimp intestine and sediment habitats in the shrimp cultural ponds. Our results found that the numbers of rare operational taxonomic units (OTUs) (6,003, 4,566 and 8,237 OTUs of water, intestine and sediment) was dozens of times more than abundant ones (only 199, 157 and 122 OTUs of water, intestine and sediment). The community diversity of abundant and rare microbial taxa was markedly different, as well as their taxonomic composition. Despite different diversity, similar abundance-occupancy relationship and biogeographic patterns between the abundant and rare microbial communities were observed, with much stronger obvious distance-decay relationships for rare community than abundant community. Furthermore, stochastic processes dominated the community assemblies of both abundant and rare microbial taxa, and deterministic process contributed more microbial community variation to rare taxa than abundant taxa. All the findings advance our understanding on the community assembly strategies of abundant and rare microbial taxa and prompt the contributions of abundant and rare microbial community to the aquatic ecosystems, which will improve aquaculture management strategy.